Analysis of the questions of the book Islamic Education for the twelfth grade in Jordan in the light of Bloom's knowledge pyramid - alkhawaldeh, Nayef Mohammad (Journal of Educational and Psychological Sciences, 2019)
The study aimed to know the quality of the questions of the book of Islamic education for the twelfth gradein Jordan, in the light of Bloom's knowledge pyramid; to reveal the levels of questions contained in the book, and to identify the percentages obtained by each level of the pyramid. To achieve the objectives of the study was used descriptive analysis method, where the researcher designed an analysis form consisted of six levels: (knowledge, understanding and comprehension, application, analysis, synthesis and evaluation)..The results of the study showed that the total number of questions in the book of Islamic Education reached (237), where the first level (knowledge) was 67.1%, the level of understanding and comprehension was (32.1%), (0.8%). The results also showed that there were no questions to measure the levels of application, analysis andsynthsis at all..
Keywords: Question analysis; Islamic education book; grade 12; Bloom's knowledge pyramid